Implementation of a Standardized Protocol for Telehealth Provider in Triage to Improve Efficiency and ED Throughput: A Quality Improvement Project. (October 2022) - Fleming, Adam; Whitty, Kristin
Abstract : There has been a significant rise in the number of emergency department (ED) visits over the past 15 years despite the number of ED providers and treatment spaces remaining fixed (M. P. Lin et al., 2018 ). A hospital's need to quickly initiate care upon patient arrival is of paramount importance to combat these ED overcrowding trends. A teleprovider in triage (TPIT) program without a standardized operating protocol leads to significant provider practice variations and limits effectiveness of a TPIT program. The intention of this health care project was to reduce ED time metrics and reduce the number of patients who left before evaluation by implementing a standardized TPIT protocol. This standardization allowed for a more predictable experience for the patient and ED staff. This quality improvement project involved developing and implementing a standardized TPIT protocol to improve TPIT efficiency and throughput. Patient ED visit metrics were collected during the pre- and postimplementation periods to evaluate for any improvement in throughput due to the TPIT protocol. The TPIT advanced practice providers (APPs) showed significant improvement in knowledge following the TPIT protocol education with an increase in provider comfort ( p < 0.05). Time spent by the TPIT provider on each patient encounter was reduced by 23%, demonstrating increased provider efficiency. Improvements in discharge lengths of stay (LOS) ( p = 0.68) and room to discharge LOS ( p < 0.05) were noted following the implementation of the TPIT protocol. Conclusions: The implementation of the TPIT protocol provided improvements in APP knowledge and understanding of the process while increasing provider efficiency. Improvements were identified in specific ED patient metrics demonstrating the significance of the TPIT protocol on patient care.